2007
DOI: 10.1007/s10832-007-9007-8
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric relaxation and variable-range-hopping conduction in BaSn1−x Cr x O3 system

Abstract: The possibility of formation of a solid solution in the system BaSn 1−x Cr x O 3 has been explored upto x≤0.20. It has been confirmed that single phase solid solution forms upto x≤0.10. Dielectric and conduction behaviour of single phase samples have been studied in the temperature range 400-610 K and frequency range 10 Hz-2 MHz. Two dielectric relaxation processes in two different frequency ranges have been observed. The temperature dependence of both dc and ac resistivity obey relation ρ=ρ o exp(B/T 1/4 ), i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…It is observed that at (5 and 10 kHz), strong dispersion is observed in the temperature range 27-60 °C, thereafter linearly with increasing temperature observed that as temperature increases, constant decreases linearly. Dielectric constant of BCR5 materials is 47 at 500 °C [6] for 1 dielectric constant obtained here is ~1300 times higher than that of BCR materials at RT. The BSO NSs exhibit space charge polarization due to their structural inhomogeneit confirmed by SEM observation.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…It is observed that at (5 and 10 kHz), strong dispersion is observed in the temperature range 27-60 °C, thereafter linearly with increasing temperature observed that as temperature increases, constant decreases linearly. Dielectric constant of BCR5 materials is 47 at 500 °C [6] for 1 dielectric constant obtained here is ~1300 times higher than that of BCR materials at RT. The BSO NSs exhibit space charge polarization due to their structural inhomogeneit confirmed by SEM observation.…”
Section: Resultsmentioning
confidence: 63%
“…This can be polarization mechanisms crease of dielectric temperature below 80 °C up attributed to the existence of space charge C, the orientational polarization is the dominant mechanism and the steep stant below 40 °C is due to when an electric field is with temperature at k and 1M Hz are at low frequencies ng dispersion is observed in ε r for , thereafter it decreases temperature. Further, it is observed that as temperature increases, dielectric Dielectric constant of [6] for 1 kHz. But the is ~1300 times higher of BSO NS for various exhibit space charge polarization their structural inhomogeneities, which are observation.…”
Section: Resultsmentioning
confidence: 97%
“…In order to modify suitably the properties of ASnO 3 (A = Ba, Sr) many substitutions have been carried out at A and Sn sites (Trari et al 1994;Parkash et al 1996;Thangadurai et al 2002;Bajpai et al 2003;Kumar et al 2005;Upadhyay et al 2007). Kumar et al (2006) studied the effect of microstructure on the properties of Sr substituted BaSnO 3 synthesized ceramic method.…”
Section: Introductionmentioning
confidence: 99%
“…Sb, Cr, and Ni ions were chosen as donor or acceptor dopants to study their structure, electrical conduction, and dielectric behavior of BaSnO 3 ceramics. [15][16][17] Mn-and Fe-doped BaSnO 3 were found to possess room-temperature ferromagnetism, 18,19 Sr-and Pb-doped BaSnO 3 were proved to have photocatalytic activity. 20,21 Though polycrystalline doped BaSnO 3 ceramics may have sufficient properties for studies and some applications, due to the inevitable effects of a large number of grain boundaries on their properties in the bulk polycrystalline ceramics, the superior properties of epitaxial films are much more attractive from the viewpoint of basic science and application in devices, especially based on heteroepitaxial structures.…”
mentioning
confidence: 99%